Gene Expression Analysis in Cold Stress Conditions Reveals BBX20 and CLO as Potential Biomarkers for Cold Tolerance in Almond - Beatriz Bielsa; Jorge Israel Ávila-Alonso; Ángel Fernández i Martí; Jérôme Grimplet; María José Rubio-Cabetas (Horticulturae, 2021)
Late spring frosts can become one of the limiting factors for the expansion of cultivation area towards a harsher climate for the almond [Prunus amygdalus Batsch syn P. dulcis (Mill.) D.A. Webb] crop as spring frost can damage up to 90% of the harvest. In order to identify key genes favoring cold tolerance in almonds, branches from three late-blooming genotypes: ‘Guara’, ‘Soleta’ and ‘Belona’ were exposed at −4 °C during 24 h in a constant climate chamber. Phenotype analysis showed that ‘Guara’ and ‘Soleta’ had a greater acclimation capacity to cold than ‘Belona’. The qRT-PCR BioMark System technology was used to monitor the relative expression of 30 candidate genes with a potential relation to cold response, which are either involved in the ICE-CBF-COR pathway or the independent CBF pathway, and also genes not yet characterized or with unknown function in almond genome. Differences in the gene expression profiles were found among the three studied genotypes and the three time-points of cold exposure (0, 2 and 24 h). BBX20 and CLO genes behaved as differentiator genes between tolerant and susceptible genotypes in cold stress response in almond pistils. In addition, the differences of expression among the tolerant genotypes suggested the intervention of different mechanisms responding to cold stress in almonds.